Animal Bite and Rabies Postexposure Prophylaxis Reporting—United States, 2013. Issue 3 (May 2015) - Vora, Neil M.; Clippard, Jessie R.; Stobierski, Mary Grace; Signs, Kimberly; Blanton, Jesse D.
<x xml:space="preserve">Abstract</x> Context: Rabies virus causes a fatal encephalitis and is typically acquired through the bite of an infected mammal. Rabies is preventable through administration of rabies postexposure prophylaxis (PEP), but this must be balanced with the need to avoid unnecessary PEP use. Though not nationally notifiable, some state health departments (SHDs) have made animal bites and use of PEP reportable within their jurisdictions. Objective: We evaluated whether animal bites and PEP were reportable to SHDs as of 2013 for every state in the United States. Design: The list of reportable conditions for each SHD as of 2013 was reviewed on the Internet for every state in the United States to determine whether animal bites or PEP were reportable. We then contacted an SHD representative (typically the State Public Health Veterinarian) to confirm data generated through Internet searches. Health departments in states where PEP was reportable were asked to complete a follow-up survey. Results: Animal bites and PEP both were reportable in 9 states (18%). Another 9 states (18%) mandated animal bite reporting but not PEP reporting, while 12 states (24%) mandated PEP reporting but not animal bite reporting. These events were not reportable in 20 states (40%). The benefits reported by personnel from SHDs with PEP reporting systems varied greatly. Conclusions: Additional investigations focusing on the value of information returned by PEP reporting and identifying best practices for implementation and management are needed. The lack of standardization between current animal bite and PEP reporting systems limits completeness of reporting and comparability of outcomes. National recommendations to standardize case definitions and other data elements might help jurisdictions developing new animal bite or PEP reporting systems.